Experimental and numerical research of crack propagation process and energy dissipation law of grouting specimens under radial impact load - Zhu, Chang-Xing; Sun, Jia-Xin; Gong, Jian; Wang, Feng-E (Frontiers in Earth Science, 2023)
Different air pressures are used to conduct an impact test based on the split Hopkinson pressure bar (SHPB) test system to study the crack evolution process and energy dissipation law of the cemented rock under impact load. The failure mechanism of the specimens is analyzed from the perspective of dynamic failure process and energy dissipation. The spatial distribution of the specimen components visualized by the image reconstruction technology and the LS-DYNA mesoscopic model is established. Results show that the proportion of dissipated energy, the dynamic tensile strength and peak strain of the specimens increase with strain rate increase. The crack evolution process of the model is quantitatively described under an impact load, which is divided into four stages, namely, no crack stage, slow development stage, accelerated propagation stage and penetration stage. Compared with the indoor and simulation test result, the crack evolution process and failure modes are consistent under different strain rates. When the specimens are destroyed, the energy dissipation rate fluctuates from 10% to 13%. The dissipated energy of cement paste accounts for more than 90% of the total dissipated energy. The cement paste damages first and its strength has a great influence on the strength of the grouting specimens. This study provides a reference to evaluate the cemented rock under a dynamic load.